Vein Stripping Versus No Stripping in Varicose Vein Disease - Muhammad Afzal, Muhammad Umair Samee, Dileep Kumar, Nisar Ahmed, Shahid Hussain Mirani (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To comparative analysis of vein stripping versus no stripping in varicose vein disease. Study design: Comparative study Place and duration of study: Department of Surgery, CMH Kharian Medical College, Kharian from 01-01-2019 to 31-12-2021. Methodology: Eighty cases of varicose vein which were having sapheno-femoral valve incompetence as well as perforators-incompetence were enrolled. The age of the cases was between 16 and 70 year. Electrocardiography (ECG), as well as venous Doppler of the affected limb was accomplished. Each group comprised 40 cases. Group A and Group B were constituted in accordance to difference in the operating procedure where vein stripping was done in Group A and without vein stripping was conducted in Group B. Results: The mean age of the patients was 42.3±4.5 years. There was higher number of females than males in this study. In the present study there were higher cases of hematoma observed in group A than in Group B with a percentage difference of 27.7% to 4.4% which was statistically significant. Ambulation comfort was observed higher in cases with ligation then having venous stripping. Pain relief of the patients post 2 months of the surgery was analyzed as higher in the Group A such as venous stripping group in comparison with the without venous stripping group (Group B). Conclusion: The technology of ligation where no vein stripping is conducted is more efficient and reliable then vein stripping methods in terms of pain, hematoma reduction, and trauma reduction with augmenting ambulation comfort. Keywords: Varicose, Mortality, Peroneal vein, Tibia, Femor